Kinetic Resolution of 2H‐Azirines by Asymmetric Imine Amidation. Issue 34 (7th July 2016) - Hu, Haipeng; Liu, Yangbin; Lin, Lili; Zhang, Yuheng; Liu, Xiaohua; Feng, Xiaoming
Abstract: Highly efficient kinetic resolution of 2 H ‐azirines by an asymmetric imine amidation was achieved in the presence of a chiral N, N ′‐dioxide/Sc III complex, thus providing a promising method to obtain the enantioenriched 2 H ‐azirine derivatives and protecting‐group free aziridines at the same time. It is rare to find an example of N1 of an oxindole participating in a reaction over C3. Moreover, chiral 2 H ‐azirines were stereospecifically transformed into an unprotected aziridine and α‐amino ketone. Abstract : The s factor : The title reaction was achieved in the presence of the chiral N, N ′‐dioxide/Sc III complex. The method provided a promising approach for obtaining the enantioenriched 2 H ‐azirine derivatives and protecting‐group free aziridines with excellent results (up to >99 % ee and 99 % ee, >19:1 d.r.).